THE CORRELATION BETWEEN MOTIVATION AND SPEAKING ABILITY OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 3 MENGWI IN ACADEMIC YEAR 2020/2021 - Ni Made Ade Sandayana Dewi; Ida Ayu Made Sri Widiastuti; I Ketut Wardana (Academic Journal on English Studies (AJOES), 2021)
The study aims at figuring out whether there is or not the correlation between motivation andspeaking ability of the eighth-grade students of SMP Negeri 3 Mengwi in the academic year 2020/2021.The present study used ex-post facto research with correlation design. In this research, there were 36students taken from the eighth grade class of SMP Negeri 3 Mengwi. In collecting the data, theresearcher used a questionnaire that was on the types of motivation by Ryan & Deci (2000). Besides,the researcher used a speaking test by administering the descriptive monologue. The result showed thatthe students’ total score for motivation resulted in 2637, and the speaking ability was 2985. Those datawere analyzed by using SPSS 23.0, which is consisted of the Normality test, Homogeneity test, PearsonProduct Moment, and T-testing. For the result of this research, the hypothesis was significantlyaccepted. According to Pearson Product Moment’s result, the r-value was 0.366, and the significancevalue was 0.014. It shows a significant correlation between motivation and speaking ability of theeighth-grade students of SMP Negeri 3 Mengwi in the academic year 2020/2021. It lies between 0.200– 0.400, which is at a low level.